Glucocorticoid receptor function in health and disease. (24th February 2015) - Caratti, Giorgio; Matthews, Laura; Poolman, Toryn; Kershaw, Stephen; Baxter, Matthew; Ray, David
Summary Glucocorticoid hormones are essential for life in vertebrates. They act through the glucocorticoid receptor (GR), which is expressed in virtually all cells of the human body. Yet the actions of glucocorticoids (GCs) are specific to particular cell types. Broadly GCs regulate carbohydrate metabolism, inflammation, stress and cell fate. Synthetic GCs are widely used in medicine and are by far the most frequent cause of Cushing's syndrome in routine practice. The advent of novel drugs targeting the GR offers new opportunities to treat patients with immune, or malignant disease, and may also offer new opportunities to manage patients with adrenal insufficiency also. This review covers the latest understanding of how GCs work, how their actions are affected by disease, and where the new drugs may take us.